Challenges for a Safe Workplace and Cope Up Strategy : A Case Study for Construction Industry in Sarawak, Malaysia - Mohammad Fazley Hossain, Chowdhury; Rusli, Ahmad (UNIMAS Publisher, 2018)
Like many other parts of the globe, in Malaysia, construction industry has a vital support to the national economy, even though statistics indicates that, at the same time, it is an extremely risky profession due to high accident rate. In addition, current evidences suggest that, in general, safety in Sarawak construction industries lack attention. As, human behavior is regarded as the principal component that contributes to accidents in this industry, this study intends to explore existing barriers in development and maintaining safety performance behavior as well as possible coping strategies. A qualitative analysis of in-depth interview (N=4) among different levels of professions within industries in Kuching, Sarawak reveals that, price sensitive subcontracting, short-term projects, irregular cash flow, dependency on larger companies, less managerial and supervisory engagement, and priority on progress alone create obstacles for safety behavior. On the other hand, possibly, the challenges can be managed through integration of safety into contracts as compliance, associated disbursement, and introducing incentives.